2017
DOI: 10.1038/srep41604
|View full text |Cite|
|
Sign up to set email alerts
|

Phytosterol esters attenuate hepatic steatosis in rats with non-alcoholic fatty liver disease rats fed a high-fat diet

Abstract: Given the adverse effects of drugs used for NAFLD treatment, identifying novel and effective natural compound to prevent NAFLD is urgently needed. In the present study, the effects of phytosterol esters (PSEs) on NAFLD were explored. Adult SD rats were randomized into five groups: normal chow diet (NC), high-fat diet (HF), low-, medium- and high-dose PSE treatment plus high-fat diet groups (PSEL, PSEM, and PSEH). Our results showed that the levels of LDL-C in the PSEL group and hepatic TG, TC, and FFA in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 44 publications
11
45
2
Order By: Relevance
“…4 b, c). In addition, the high-fat diet leads also to a hepatic steatosis condi-tion, which can evolve into fibrosis and hepatic cirrhosis, and to a low-grade, systemic and chronic inflammatory state [29][30][31]. Several pre-clinical studies showed that C. bergamia promotes significant anti-inflammatory effects both at a systemic and tissue level [18,32].…”
Section: Resultsmentioning
confidence: 99%
“…4 b, c). In addition, the high-fat diet leads also to a hepatic steatosis condi-tion, which can evolve into fibrosis and hepatic cirrhosis, and to a low-grade, systemic and chronic inflammatory state [29][30][31]. Several pre-clinical studies showed that C. bergamia promotes significant anti-inflammatory effects both at a systemic and tissue level [18,32].…”
Section: Resultsmentioning
confidence: 99%
“…However, hematoxylin–eosin staining of liver sections revealed no morphological alterations in either AO or OO group (data not shown). The effect of AO on ALT activity is likely to be related to the phytosterol composition of this oil [ 22 ]. Hepatotoxicity of LPS was revealed by significant increases in circulating transaminases activities, including alanine aminotransferase (ALT, +67%) and aspartate transaminase (AST, +21%) activities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, hepatic inflammatory stress was decreased through cytokine inhibition (IL-10, TGF-β, IL-6) and oxidative stress was reduced via antioxidative enzymes and reduced MDA contents. A CRP factor, recognized as cardiovascular disease (CVD) risk factor, was enhanced in NAFLD disease which upon PSE treatment was reduced which confirmed the anti-inflammatory potential of PSEs [130].…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 63%